2020
DOI: 10.17058/jeic.v10i3.14984
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis: prevalence, risk profile and association with sexually transmitted infections

Abstract: Background and Objectives: Bacterial vaginosis (BV) is the most common cause of vaginal discharge in the world. The study aimed to estimate the prevalence and to identify risk factors associated with bacterial vaginosis. Methods: A cross-sectional study was conducted in Ouro Preto, Brazil, between February and December 2017. Three hundred and forty-one women aged 18 years or older, users of the Brazilian Unified Health System, participated in this study. Women who used oral or topical antibiotics in the four w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
1
1
1
1
Order By: Relevance
“…In this study, there were no statistically significant association between bacterial vaginosis and sociodemographic characteristics of participants such as age, marital status, residence, occupation and level of education (P>0.05). This is in line with studies conducted in Tanzania, 38 Brazil 37 and Turkey. 56 But, studies conducted in the USA, Poland, China, Indonesia and Nigeria 32 , 57–60 revealed an association between BV and different sociodemographic characteristics such as marital status, age, level of education and occupational status.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, there were no statistically significant association between bacterial vaginosis and sociodemographic characteristics of participants such as age, marital status, residence, occupation and level of education (P>0.05). This is in line with studies conducted in Tanzania, 38 Brazil 37 and Turkey. 56 But, studies conducted in the USA, Poland, China, Indonesia and Nigeria 32 , 57–60 revealed an association between BV and different sociodemographic characteristics such as marital status, age, level of education and occupational status.…”
Section: Discussionsupporting
confidence: 90%
“…However, this study found a lower prevalence of bacterial vaginosis compared with a study done in Brazil, Ouro Preto 32.5% (95% CI: 27.7, 37.7), 37 Tanzania 28.5%, 38 Ghana 30.9%, 39 Zimbabwe 32.6%, 40 Nigeria 38% 41 and Sudan 49.8%. 2 The lower prevalence of BV in the current study might be attributed to the difference in sampling techniques, sample size difference and other sociodemographic characteristics of the participants.…”
Section: Discussioncontrasting
confidence: 88%
“…the positive association between the infections and young age is due to more sexual activity of younger women increasing their susceptibility to sexually transmitted infections. In several studies, socioeconomic status affecting Pap smear results was reported due to few health check-ups and poor hygiene (28)(29)(30). Studies found age and socioeconomic status to be critical factors in cervical cancer screening, affecting Pap smear test results.…”
Section: Discussionmentioning
confidence: 99%
“…A vaginose bacteriana (VB) é a principal causa de vulvovaginite em mulheres em idade reprodutiva 1 , com prevalência variável em diferentes localidades de cerca de 32% no Brasil e de 40 a 60% na Etiópia. É resultado do desequilíbrio da microbiota vaginal, com redução da concentração de bactérias protetoras, como Lactobacillus, e aumento do pH e da concentração de bactérias patogênicas, como Gardnerella vaginallis e Mobiluncus spp [2][3][4] .…”
Section: /9 Introduçãounclassified